Contribution of Gut Microbiota to Immunological Changes in Alzheimer’s Disease - van Olst, Lynn; Roks, Sigrid J.M.; Kamermans, Alwin; Verhaar, Barbara J. H.; van der Geest, Anne M.; Muller, Majon; van der Flier, Wiesje M.; de Vries, Helga E. (Frontiers in Immunology, 2021)
Emerging evidence suggests that both central and peripheral immunological processes play an important role in the pathogenesis of Alzheimer’s disease (AD), but regulatory mechanisms remain unknown. The gut microbiota and its key metabolites are known to affect neuroinflammation by modulating the activity of peripheral and brain-resident immune cells, yet an overview on how the gut microbiota contribute to immunological alterations in AD is lacking. In this review, we discuss current literature on microbiota composition in AD patients and relevant animal models. Next, we highlight how microbiota and their metabolites may contribute to peripheral and central immunological changes in AD. Finally, we offer a future perspective on the translation of these findings into clinical practice by targeting gut microbiota to modulate inflammation in AD. Since we find that gut microbiota alterations in AD can induce peripheral and central immunological changes via the release of microbial metabolites, we propose that modulating their composition may alter ongoing inflammation and could therefore be a promising future strategy to fight progression of AD.